2021
DOI: 10.1093/infdis/jiaa774
|View full text |Cite
|
Sign up to set email alerts
|

Entomological and Anthropological Factors Contributing to Persistent Malaria Transmission in Kenya, Ethiopia, and Cameroon

Abstract: Introduction In order to improve our understanding of the fundamental limits of core interventions and guide efforts based on prioritization and identification of effective/novel interventions with great potentials to interrupt persistent malaria transmission in the context of high vector control coverage, the drivers of persistent disease transmission were investigated in three eco-epidemiological settings; forested areas in Cameroon, coastal area in Kenya and highland areas in Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 59 publications
8
31
0
Order By: Relevance
“…Thus, the contribution of outdoor biting to malaria persistence could be much higher as universal coverage of ITNs and IRS has not been achieved. A multicountry study in Cameroon, Kenya and Ethiopia found high malaria transmission outdoors compared to indoors 5 . While this phenomenon is not new 9 11 , the profile of vectors implicated in outdoor transmission could differ in different eco-epidemiologic settings 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the contribution of outdoor biting to malaria persistence could be much higher as universal coverage of ITNs and IRS has not been achieved. A multicountry study in Cameroon, Kenya and Ethiopia found high malaria transmission outdoors compared to indoors 5 . While this phenomenon is not new 9 11 , the profile of vectors implicated in outdoor transmission could differ in different eco-epidemiologic settings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A multicountry study in Cameroon, Kenya and Ethiopia found high malaria transmission outdoors compared to indoors 5 . While this phenomenon is not new 9 11 , the profile of vectors implicated in outdoor transmission could differ in different eco-epidemiologic settings 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, An. coustani , was found being infected with Plasmodium species [ 56 ] showing evidence of possible malaria transmission by An. coustani in the country.…”
Section: Discussionmentioning
confidence: 99%
“…The Ministry of Health of the Republic of Indonesia reports that 97% of malaria cases in Indonesia occur in Papua, where malaria is endemic and common, as evidenced by an API value (Annual Parasite Index) greater than 5/1000 population ( Kemenkes, 2018 ). Geographic conditions, population characteristics, the presence of vectors, and inadequate health services also contribute to malaria transmission ( Hasyim, Dale, Groneberg, Kuch, & Müller, 2019 ; Bamou et al., 2021 ; Meireles, De Souza Sampaio, Monteiro, & Goncalves, 2020 ). Consequently, malaria cases occur throughout the year ( Lawpoolsri et al., 2019 ) and people living in endemic areas can potentially suffer from recurrent malaria.…”
Section: Introductionmentioning
confidence: 99%